2018
DOI: 10.1016/j.antiviral.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Transient inhibition of sphingosine kinases confers protection to influenza A virus infected mice

Abstract: Influenza continues to pose a threat to public health by causing illness and mortality in humans. Discovering host factors that regulate influenza virus propagation is vital for the development of novel drugs. We have previously reported that sphingosine kinase (SphK) 1 promotes influenza A virus (IAV) replication in vitro. Here we demonstrate that the other isoform of SphK, SphK2 promotes the replication of influenza A virus (IAV) in cultured cells, and temporary inhibition of SphK1 or SphK2 enhances the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 54 publications
6
59
0
Order By: Relevance
“…Moreover, de novo synthesis of ceramide was found to be upregulated in cells overexpressing S1P lyase (74). Therefore, our results complement the previous findings since S1P formation will reduce the cellular ceramide pool and thus increasing IAV replication (49,71,72). Ceramide analogues and mimetics have been proposed as potential immunotherapeutic remedies against viral infections (45).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, de novo synthesis of ceramide was found to be upregulated in cells overexpressing S1P lyase (74). Therefore, our results complement the previous findings since S1P formation will reduce the cellular ceramide pool and thus increasing IAV replication (49,71,72). Ceramide analogues and mimetics have been proposed as potential immunotherapeutic remedies against viral infections (45).…”
Section: Discussionsupporting
confidence: 87%
“…Our data, as well as those previously published (49,71,72), suggest that ceramide and downstream products likely interferes with the IAV life cycle at various stages, including replication, protein transport, and assembly. Confirming the biological significance of our results in vivo is something that we are planning to investigate in future work.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…SphK1 inhibition also altered the phosphorylation of ERK, p90RSK, and AKT, the upstream signals of RanBP3/CRM1 activation. In a later study, our lab found that inhibition of SphK1 protects mice against lethal challenge with IAV [60]. Therefore, harnessing SphK1 appears to be critical for effective IAV infection in vitro and in vivo.…”
Section: Sphk1 In Virus Replicationmentioning
confidence: 90%
“…Sphingosin kinases (SphK) are lipid kinases that mediate conversion of sphingosine to bioactive lipid sphingosine 1phosphate (S1P) (67), a known modulator of central apoptotic pathways (68). IAV infections leads to increased expression and activation of SphK1 and SphK2 (29) and in vitro inhibition of SphK1 was shown to decrease IAV RNA synthesis via suppression of NFkB activation (69). Treatment of mice with specific inhibitors to either SphK1 or SphK2 or a pan-SphK inhibitor led to prolonged survival of mice following lethal IAV infection (29).…”
Section: Therapeutic Small Moleculesmentioning
confidence: 99%